Acoustic and Lad Aspects of Traditional Music - Axmedov Sharifjon Mamirdjanovich (Researchparks Publishing, 2021)
Information has been given about the very high level of development of culture and art in Central Asia from time immemorial, specific types of art such as classical art, historical monuments, miniature art, architecture, oral and written creativity of the people. We can see what is known about the monuments of fine art found in archaeological excavations in various oases of our country.